Public Services Quality in Kantor Koperasi & UMKM at West Sumatra, Indonesia - Anggun Anggun (Institute of Multidisciplinary Research and Community Service, 2022)
Abstract: In this study the method used was descriptive qualitative research method, the purpose of this research was to understand how quality of Kantor Kooperasi dan UMKM at the West Sumatra and the inhibiting factors for service quality at these institutions, how the efforts are made by these agencies and whether the quality of service is in accordance with expectations society or not. The source of data used in this study uses primary data or data obtained from direct agencies. Based on my observation that the quality of service at the Kantor Kooperasi dan UMKM of West Sumatra Province can be said to be good, which relates to Tangible aspects, Reliability, Responsiveness, Assurance and Emphaty. (Empathy). Based on the observations that I have made, there are still problems and inadequacies in the quality of service at these agencies, namely the lack of complete facilities or infrastructure, supporting infrastructure, services that are still old, while the quality of service at Kantor Kooperasi dan UMKM of West Sumatra Province has been said to be good because through observation and The interviews I conducted directly revealed that the employees at the agency were responsive in serving the community, friendly, polite and courteous in serving the community and responding and responding quickly to the community's goals for the agency. As well as the caring nature that is also shown by the employees at the agency and also does not discriminate between services to everyone Keywords: public service, good governance, descriptive qualitative research.